2022
DOI: 10.3389/fpsyg.2021.777102
|View full text |Cite
|
Sign up to set email alerts
|

Psychodynamic Therapist’s Subjective Experiences With Remote Psychotherapy During the COVID-19-Pandemic—A Qualitative Study With Therapists Practicing Guided Affective Imagery, Hypnosis and Autogenous Relaxation

Abstract: The COVID-19-pandemic brought massive changes in the provision of psychotherapy. To contain the pandemic, many therapists switched from face-to-face sessions in personal contact to remote settings. This study focused on psychodynamic therapists practicing Guided Affective Imagery, Hypnosis and Autogenous Relaxation and their subjective experiences with psychotherapy via telephone and videoconferencing during the first COVID-19 related lockdown period in March 2020 in Austria. An online survey completed by 161 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
12
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 43 publications
4
12
0
7
Order By: Relevance
“…Technical problems were also reported in other studies from the same period [ 41 , 42 ]. As also noted by Jesser et al [ 43 ] and Eichenberg et al [ 44 ], therapists tried to compensate for the lack of non-verbal communication by focusing on other channels of perception. The respondents described this as exhausting and tiring, a finding that was also echoed by other authors [ 21 , 39 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Technical problems were also reported in other studies from the same period [ 41 , 42 ]. As also noted by Jesser et al [ 43 ] and Eichenberg et al [ 44 ], therapists tried to compensate for the lack of non-verbal communication by focusing on other channels of perception. The respondents described this as exhausting and tiring, a finding that was also echoed by other authors [ 21 , 39 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As also noted by Jesser et al [ 43 ] and Eichenberg et al [ 44 ], therapists tried to compensate for the lack of non-verbal communication by focusing on other channels of perception. The respondents described this as exhausting and tiring, a finding that was also echoed by other authors [ 21 , 39 , 43 ]. The lack of a non-verbal level affected the therapeutic process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ob Personen, die nicht sichtbar waren, ebenfalls "mit dabei" waren, war auch nicht immer klar. Derartige Beobachtungen sind auch aus anderen Untersuchungen bekannt -selbst in Erwachsenenpsychotherapien haben Patient*innen nicht immer die Möglichkeit, sich für die Psychotherapie einen geschützten Raum in den eigenen vier Wänden zu schaffen (Jesser et al 2022b). Diese Einschränkung muss sehr kritisch gesehen werden.…”
Section: Diskussionunclassified
“…Most interestingly, many therapists felt a need to compensate for the lack of physical presence. An Austrian survey on 161 psychodynamic therapists by Jesser et al (2021Jesser et al ( , 2022 revealed that transference and countertransference processes and the intensity of the therapeutic process changed the most. Moreover, the therapists experienced some of their patients to have difficulties in establishing a safe space at home, severe limitations of sensory perception, and an inferior relationship in the context of the remote setting.…”
mentioning
confidence: 99%